Barriers and Mitigation Strategies in Stigma toward Infectious Diseases: Psychological, Social, and Healthcare Implications - Maulia, Jihan Tasyabitah Tri (Yayasan Sinergi Kawula Muda, 2022)
Stigma associated with infectious diseases presents a significant barrier to healthcare access, treatment adherence, and overall well-being. This study systematically examines the psychological, social, economic, and healthcare-related consequences of stigma, emphasizing its impact on individuals diagnosed with HIV, tuberculosis, and COVID-19. A comprehensive literature review was conducted across multiple academic databases, focusing on peer-reviewed studies published within the last ten years. Findings indicate that stigma contributes to heightened mental health challenges, including anxiety, depression, and social isolation, while also negatively influencing employment and healthcare-seeking behaviors. Systemic factors, including policy deficiencies, cultural beliefs, and media representation, further perpetuate stigma and hinder effective intervention efforts. Successful stigma-reduction programs highlight the importance of community engagement, educational campaigns, and healthcare provider training in fostering a more inclusive environment for affected individuals. The study underscores the necessity of policy reforms that protect patient confidentiality and promote non-discriminatory healthcare practices. Future research should explore culturally specific interventions and longitudinal assessments of stigma-related experiences to enhance public health strategies. Addressing stigma requires a multifaceted approach integrating policy, education, and community-driven initiatives to improve health outcomes and quality of life for individuals with infectious diseases.